Husbandry factors and the resumption of luteal activity in open and zero-grazed dairy cows in urban and peri-urban Kampala, Uganda - Kanyima, B.M.; Båge, R.; Owiny, D.O.; Ntallaris, T.; Lindahl, Johanna F.; Magnusson, Ulf; Nassuna-Musoke, M.G. (Wiley, 2014)
The study investigated the influence of selected husbandry factors on interval to resumption of post-partum cyclicity among dairy cows in urban and peri-urban Kampala. A prospective study of 85 day post-partum period of 59 dairy cows in open (n = 38) and zero grazing (n = 21) systems was conducted on 24 farms. Cows of parity 1–6 were recruited starting 15–30 days post-partum. Progesterone (P4) content in milk taken at 10–12 day intervals was analysed using ELISA. The cow P4 profiles were classified into ‘normal’ (< 56 days), ‘delayed’ (> 56 days), ‘ceased’ or ‘prolonged’ (if started < 56 days but with abnormal P4 displays) resumption of luteal activity and tested for association with husbandry and cow factors. Of the 59 cows, luteal activity in 81.4% resumed normally and in 18.6%, delayed. Only 23.7% maintained regular luteal activity, while the others had ceased (10.2%), prolonged (37.3%) or unclear luteal activity (20.3%). There were no differences between open and zero-grazed cows. Milk production was higher (p < 0.05) in zero than open grazing, in urban than peri-urban and in cows fed on brew waste (p < 0.001) compared with mill products and banana peels. Results suggest that luteal activity resumes normally in a majority of cows, although only a minority experienced continued normal cyclicity once ovulation had occurred, in the two farming systems irrespective of feed supplements or water, and that supplementing with brew waste is beneficial for milk production.